الرقمــــــنة في الإدارة المحــــــــلية بلدية حمام الضلعة نموذجا - مرزوقي مسعود - بن حليمة حسينة الرقمــــــنة في اإلدارة المحــــــــلية بلدية حمام الضلعة نموذجا الرقمــــــنة في اإلدارة المحــــــــلية بلدية (جامعة المسيلة, 2024)
Digitization is a crucial stage in the transition towards digital management, representing the clearest embodiment of technological advancement in both general administrative practices and local governance specifically. It has asserted itself as a result of numerous ramifications, serving as the greatest testament to the modernization of administration. Algeria's inclination towards such a method of governance has contributed to eliminating many complexities and issues that administration, particularly local administration, faced in its interaction with citizens. Digitization has also contributed to the development of human and organizational administration. Algeria continues to move forward in achieving a qualitative leap in managing its administrations .
Keywords: Administration - Digitization - Transition – Management- Local Administration